IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KECAMATAN BANCAR KABUPATEN TUBAN - Nadya Rindayu Farista Fanny; Suci Megawati (Publika, 2022)
Non-Cash Food Aid (BPNT) is food social assistance in the form of non-cash from the government which is regulated in the Minister of Social Affairs Regulation No. 20 of 2019 concerning the Distribution of Non-Cash Food Aid. In 2019 the BPNT program began to be implemented in the Bancar Sub-District This study aims to identify and describe the implementation of the BPNT program in Bancar Sub-District, Tuban Regency. Using a qualitative approach with a descriptive method. The focus of research on policy implementation models according to Donald Van Meter and Carl Van Horn. Data collection techniques through interviews, observation, and documentation. Data were analyzed using Miles, Huberman's analysis, namely data collection, data reduction, data presentation, and drawing conclusions. According to the findings of the study based on Donald Van Meter and Carl Van Horn's six theoretical indications, the BPNT program as a whole has been well-executed, while there are still flaws. The lack of data transmission and data synchronization across devices in the village are hurdles in the communication indicator, resulting in BPNT recipients' data not being upgraded. As a result, the researchers propose that each village head, who is the implementer in the closest scope to the recipient/KPM in this case, conducts a review or supervision of every citizen who is a target of the BPNT program assistance via RT coordination to the village head/relevant village apparatus. Keywords: Implementation, Program, Non-Cash Food Aid